ISOLATION OF BABESIA-BIGEMINA AND BABESIA-BOVIS MEROZOITES BY AMMONIUM-CHLORIDE LYSIS OF INFECTED ERYTHROCYTES - Machado, R. Z.; Valadao, CAA; Melo, W. R.; Alessi, A. C. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
1. We describe the isolation of viable merozoites from erythrocytes infected with Babesia bovis or Babesia bigemina organisms by ammonium chloride lysis.2. Parasite morphology was examined by both light and transmission electron microscopy. Erythrocyte-free parasites maintain their viability and infectivity, retain their antigenicity and are suitable for use in the indirect fluorescent antibody assay.
Keywords: BABESIA BOVIS; BABESIA BIGEMINA; MEROZOITE ISOLATION